Imperial incarceration : detention without trial in the making of British colonial Africa - Lobban, Michael (Cambridge : Cambridge University Press, 2021)
For nineteenth-century Britons, the rule of law stood at the heart of their constitutional culture, and guaranteed the right not to be imprisoned without trial. At the same time, in an expanding empire, the authorities made frequent resort to detention without trial to remove political leaders who stood in the way of imperial expansion. Such conduct raised difficult questions about Britain's commitment to the rule of law. Was it satisfied if the sovereign validated acts of naked power by legislative forms, or could imperial subjects claim the protection of Magna Carta and the common law tradition? In this pathbreaking book, Michael Lobban explores how these matters were debated from the liberal Cape, to the jurisdictional borderlands of West Africa, to the occupied territory of Egypt, and shows how and when the demands of power undermined the rule of law. This title is also available as Open Access on Cambridge Core.
Introduction -- Martial Law and the Rule of Law in the Eastern Cape, 1830-1880 -- Zulu political prisoners, 1872-1897 -- Egypt and Sudan, 1882-1887 -- Detention without trial in Sierra Leone and the Gold Coast, 1865-1890 -- Removing rulers in the Niger Delta, 1887-1897 -- Consolidating colonial rule : detentions in the Gold Coast and Sierra Leone, 1896-1901 -- Detention comes to court : African appeals to the courts in Whitehall and Westminster, 1895-1922 -- Martial Law in the Anglo-Boer War, 1899-1902 -- Martial Law, the Privy Council and the Zulu Rebellion of 1906 -- Conclusion.
Title from publisher's bibliographic system (viewed on 20 Aug 2021).
Keywords: Political crimes and offenses -- Africa, English-speaking -- History -- 19th century; Detention of persons -- Africa, English-speaking -- History -- 19th century; Political crimes and offenses -- Africa, English-speaking -- History -- 20th century; Detention of persons -- Great Britain -- Colonies -- History -- 19th century; Detention of persons -- Africa, English-speaking -- History -- 20th century; Political crimes and offenses -- Great Britain -- Colonies -- History -- 19th century; Law -- Africa, English-speaking -- English influences -- History -- 20th century; Law -- Africa, English-speaking -- English influences -- History -- 19th century; Detention of persons -- Great Britain -- Colonies -- History -- 20th century; Political crimes and offenses -- Great Britain -- Colonies -- History -- 20th century